Wybrane nieklasyczne metody estymacji : Monte Carlo, bootstrap, jackknife - Zięba, Agnieszka (Three nonclassical methods of statistical inference : Monte Carlo, bootstrap and jackknife, 2006)
This paper describes and compares three methods of statistical inference: Monte Carlo, bootstrap and jackknife. Monte Carlo methods are presented as a basis for two other methods. The wide range of applications areas of jackknife and bootstrap is shown only in selected aspects. Their application to estimating parameters and assessing statistical accuracy is considered. Moreover bootstrap and jackknife is presented as data imputation techniques.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1142, s. 62-68